The Hybridity of Scientific Knowledge: A Response to Leonardo Ambasciano - Stuckrad, Kocku von (Zygon, 2016)
This article responds to Leonardo Ambasciano's review of The Scientification of Religion: An Historical Study of Discursive Change, 1800-2000 by Kocku von Stuckrad. It criticizes a narrative that presents naturalism and science as the ultimate system of knowledge. Contesting this rhetoric, the article underscores the plurality and hybridity of knowledge systems, which is the main topic of the book under review.